Social Media as a Platform for Acquiring Medical English: Measuring Perceptions of Non-native Healthcare Providers - Wannas, Amr Selim; Hassan, Inas Hussein (ELT Worldwide: Journal of English Language Teaching, 2023)
The primary goal of this study is to measure the perceptions of non-native healthcare providers towards the role of social media in acquiring medical English and enhancing language learning autonomy, and the features of social media that help them acquire medical vocabulary. To this end, a questionnaire was constructed and disseminated to 350 Egyptian healthcare providers working at Magdi Yacoub Foundation (MYF), Aswan Heart Centre (AHC), Egypt. For data triangulation, interviews were conducted with a subset of the questionnaire takers. Findings of the study reveal that social media platforms tremendously assist non-native healthcare providers in acquiring medical English vocabulary and enhancing language learning autonomy. Among the features of social media that proved to be beneficial to Egyptian healthcare providers are easiness of usage, free-of-charge availability, ability to edit, copy and share, ability to store data forever, emoticons to express feelings, choice to join private conversations, and choice to join public discussions and debates.